English Neologisms: knowledge domains represented by them, principles and mechanisms of their creation - Liudmila V. Babina (Актуальные проблемы филологии и педагогической лингвистики, 2020)
The article considers English neologisms from the position of cognitive approach, which involves identifying knowledge domains represented by such words, describing the principles that ensure the creation of new knowledge based on existing ones. In addition, the author analyzes some cognitive mechanisms for creating neologisms that arise as a result of reinterpretation. The study was performed on the material of new language units selected on sites dedicated to English neologisms, using a continuous sampling method. The author uses a set of methods, the main of which are methods of conceptual and definition analysis and cognitive modeling. As a result of the research, it was found that neologisms represent knowledge domains that traditionally arouse interest (politics, economics, and the field of consumption). At the same time, there are many neologisms that reflect knowledge about computer and digital technologies and various types of human interaction with the virtual world. It is determined that neologisms that appear as a result of reinterpretation are created by cognitive mechanisms of “conceptual metaphor”, “conceptual metonymy”, “conceptual metaphtonymy”, and “concretization”. Neologisms are formed by the following metaphorical cognitive models: HUMAN BEING – ARTEFACT, ARTEFACT – ANIMAL, ARTEFACT – ARTEFACT, ABSTRACT – PHYSICAL, VIRTUAL – REAL, ANIMAL – ANIMAL, and HUMAN BEING – ANIMAL, which are used both when reinterpreting simple and compound words. The principles that determine the cognitive processes of creating neologisms that represent knowledge based on existing language structures are also described: principle of economy, principle of vividness and subjectivity, principle of using new interpretive realities, principle of remotivation.